Reinvigorating adolescent sexuality education through alternate reality games: the case of The Source. Issue 4 (3rd July 2016) - Bouris, Alida; Mancino, Jenny; Jagoda, Patrick; Hill, Brandon J.; Gilliam, Melissa
Abstract: This paper presents findings from a focus group study conducted to evaluate The Source, an alternate reality game (ARG). ARGs are a relatively new genre of interactive digital games that use a variety of media to engage game players. We developed modules on sexual health, sexual orientation, and homophobia in a game that was delivered to 133 predominantly African-American and Latino US youth. Ten focus groups were conducted with 43 young people aged 13–18 who played The Source to understand feasibility and acceptability issues and the impact of the game on young people's attitudes, knowledge, and behaviours. Data were transcribed and analysed for common themes by two independent coders. Four primary themes were identified: (1) the feasibility and acceptability of using an ARG for sexual education; (2) the acceptability of The Source 's specific sexual health content; (3) the game's influence on sexual health-related knowledge, attitudes, and behaviours; and (4) the impact of the game on young people's thoughts and responses to sexual orientation and homophobia. Study findings indicate that an ARG is an exciting and interactive way to educate young people on sensitive topics in sexuality education, but that attention to narrative authenticity and effective messaging are important issues to address.